Climate Change Impacts on Society and EU Political Process Towards Security Implications - Ceka, Jonka (Calitatea Vieții, 2014)
Scientific evidence, as well as human testimony exists on climate change. Its implications may affect resource availability, human health, and security, posing a threat to economic development, as well as to social and political stability. Projected climate change is expected to affect European society in all economic sectors, goods and services, with largest impacts coming indirectly from Mediterranean region. Developed countries may succeed with mechanisms, although costly, to deal with these impacts and to minimize the difficulties caused by climate change. Countries that are already facing poverty, social and political instability are expected to be more vulnerable to the negative consequences of climate change. Social innovation is a recommended tool for addressing those consequences. By the beginning of the new millennium, climate change has been increasingly addressed by EU policy-makers and analysts as a security concern. While climate change impacts have, so far, been of no major concern for the EU environmental policy, security implications of climate change have increasingly become more important for the European Commission. Hence, climate change is being intensively discussed as a human and environmental security issue in European or regional forums. Furthermore, in a world of globalisation, environmental consequences are overcoming the conventional borders. Hence, environmental cooperation and political integration in the framework of climate change are appropriate policies.